Intron sequence directs RNA editing of the glutamate receptor subunit GluR2 coding sequence. - Egebjerg, J (1994)
The Ca2+ permeability and the rectifying properties of the glutamate receptors assembled from the subunits GluR1-GluR4 depend upon a critical Arg in the GluR2 subunit located in a domain that has been proposed to span the membrane. The GluR2 subunit gene encodes a Gln (CAG) at this position, whereas the mRNA is edited so that it encodes an Arg (CGG) at this position [Sommer, B., Kohler, M., Sprengel, R. & Seeburg, P. H. (1991) Cell 67, 11-20]. The editing process is specific since only the GluR2 subunit RNA is edited even though the GluR1, GluR3, and GluR4 RNAs have a similar sequence. We show that this selective RNA editing depends upon a critical intron sequence in the GluR2 gene. This critical intron sequence is sufficient to cause editing of the GluR3 subunit exon in a chimera minigene constructed so that the GluR3 exon is placed upstream to the GluR2 intron sequence. Transfections of a neuronal cell line, N2a, with minigene constructs encoding different fragments of the GluR2 gene demonstrate that the 5' part of the 3' intron is essential for editing. Part of the exon and this critical intron sequence contains an inverted repeat that can fold into a structure consisting of three helical elements. Similar conclusions were reached by Higuchi, M., Single, F. n., Köhler, M., Sommer, B., Sprengel, R. & Seeburg, P. H. [(1993) Cell 75, 1361-1370]. These experiments demonstrate that the low Ca2+ permeability of the ionotropic non-N-methyl-D-aspartate glutamate receptors depends upon RNA editing, which requires a sequence in an intron 3' to the exon.